1986
DOI: 10.1002/etc.5620050704
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration of hydrophobic chemicals in fish: Relationship with membrane permeation

Abstract: A model is presented for the bioconcentration in fish of nonpolar hydrophobic chemicals that are not metabolized. The model assumes that diffusion rates through membrane‐diffusion layer barriers influence uptake and depuration kinetics in fish. For extremely hydrophobic (log Kd, oct > 3 to 4) chemicals, uptake rate constants in fish are independent of the solute's hydrophobicity, whereas for low to moderately hydrophobic chemicals proportionality between these parameters is observed. Additionally, elimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(81 citation statements)
references
References 21 publications
10
70
1
Order By: Relevance
“…28) By fitting an exponential curve, S·(1−exp(−k·t)), to the reported residues in the skin when exposed to each pesticide solution (C, mg/L), the absorption rate (k, /hr) and saturated amount (S, ng/cm 2 ) were newly estimated. Very similar absorption rates (k=0.24 to 0.33) were obtained for these organochlorines in accordance with the Gobas theory, 16) and a linear correlation was observed between log (S/C) and log K ow (slope, 0.61; r 2 =0.91). As another approach, the diffusion cell apparatus, consisting of two chambers with skin clamped between them, is frequently utilized to evaluate absorption and penetration of pesticides.…”
Section: )supporting
confidence: 82%
See 1 more Smart Citation
“…28) By fitting an exponential curve, S·(1−exp(−k·t)), to the reported residues in the skin when exposed to each pesticide solution (C, mg/L), the absorption rate (k, /hr) and saturated amount (S, ng/cm 2 ) were newly estimated. Very similar absorption rates (k=0.24 to 0.33) were obtained for these organochlorines in accordance with the Gobas theory, 16) and a linear correlation was observed between log (S/C) and log K ow (slope, 0.61; r 2 =0.91). As another approach, the diffusion cell apparatus, consisting of two chambers with skin clamped between them, is frequently utilized to evaluate absorption and penetration of pesticides.…”
Section: )supporting
confidence: 82%
“…15) In contrast, the k D values of various polychlorinated biphenyls and polycyclic aromatic hydrocarbons injected into two frog species decreased in proportion to their log K ow (4 to 7). 13) Gobas et al 16) utilized the diffusion rate of a hydrophobic chemical through membranediffusion layer barriers to express the k U and k D terms in fish. Their theory suggested the increase of log k U in proportion to log K ow and the constant k D at log K ow <3 to 4, while the constant k U and the proportional decrease of log k D at log K ow >3 to 4.…”
Section: Uptake and Depurationmentioning
confidence: 99%
“…It has been shown that diffusion over the aqueous barriers is also the main rate limiting step in the membrane transport of extreme hydrophobic contaminants [12,13]. In their study with polynuclear aromatic hydrocarbons Rahman et al found a direct correlation between low aqueous solubility and increased uptake efficiency of these compounds in the presence of bile [14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, III showed a higher toxicity than II and IV to all species, but much less than I by two to three orders of magnitude to pyrethroidsensitive taxa (fish and daphnid) and one order of magnitude to pyrethroid-insensitive ones (alga). Gobas et al applied the diffusion rate of a hydrophobic chemical through membranediffusion layer barriers to express the rates of chemical uptake and elimination in fish, 22) and they suggested the constant uptake and proportional decrease in elimination with an increasing log K ow (n-octanol/water partition coefficient) above 3-4. The log K ow values of II-IV are estimated to be 3.1-3.5 by the EPI-Suite 23) and much lower than I (5.0), 14) suggesting higher elimination of these metabolites as one of the reasons for their lower toxicity.…”
Section: Discussionmentioning
confidence: 99%